ОСОБЛИВОСТІ ЗАБЕЗПЕЧЕННЯ ЕЛЕКТРОМАГНІТНОЇ СУМІСНОСТІ ДЖЕРЕЛ БЕЗПЕРЕБІЙНОГО ЖИВЛЕННЯ - Пілінський, В.В.; Швайченко, В.Б. (Інститут електродинаміки НАН України, Київ, 2024)
An overview of the main structures of uninterruptible power systems is provided. The impact on internal-system and external-system electromagnetic compatibility of these devices is determined. Contemporary standards and requirements for ensuring electromagnetic compatibility of uninterruptible power systems are analyzed. Features of the structures of uninterrupted power systems such as online, offline and line interactive by the conductive path of propagation of interference are given. The main advantages of eco uninterrupted power supply are summarized. A generalized approach is proposed for the application of radiofrequency interference filters depending on the electromagnetic environment and features of uninterruptible power systems. Refined limitations on the possibilities of adjusting the basic and influence parasitic parameters of the filter links by symmetric and asymmetric propagation of conductive disturbances. The possibility of using remote control of the effectiveness of means of reducing conductive disturbances was assessed. The expediency of localization of control parameters of smart radiofrequency interference filters with the use of artificial intelligence is determined. References 10, figures 6, tables 2.